Preparation method and application of metal diatomic polymer catalyst
By using specific aromatic monomers and aromatic amines in metal diatom polymer catalysts for Schiff base reaction, a regular metal diatom linear or planar polymer is formed, which solves the problem of metal atom spacing regulation and improves catalytic performance and reaction efficiency.
Patent Information
- Application Number
- CN202411659701.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The prior art is difficult to accurately regulate the distance between metal atoms in metal diatom polymer catalysts, resulting in insufficient catalytic reaction activity and stability, affecting catalytic performance.
By reacting Schiff base with an aromatic monomer containing aldehyde and hydroxy/sulfhydryl groups and aromatic tetramine or hexamine monomers, a metal dia linear or planar polymer coordinated by metal ions with nitrogen, oxygen or sulfur atoms on the Schiff base structure is formed, and synthesized under no pyrolysis, ensuring the structural regularity of the polymer and the preservation of the active site.
The precise regulation of the metal atom spacing in metal diatom polymer catalysts is achieved, the activity and stability of the catalytic reaction is improved, the adsorption and desorption capacity of the intermediate is optimized, the reaction energy barrier is reduced, and the catalytic reaction is promoted.
Smart Images

Figure CN119569977A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic material preparation, and in particular to a metal diatomic polymer catalyst and a preparation method and application thereof. Background Art
[0002] Since ancient times, energy has played a very important role in human development. People's food, clothing, daily necessities, housing, transportation, and industrial and agricultural production activities are inseparable from energy. Due to the mining and use of fossil fuels, environmental problems have become increasingly serious. Therefore, the development and efficient use of pollution-free sustainable energy is an effective way to solve the above problems.
[0003] For example, fuel cells, metal-air batteries, and many other energy sources can be used as energy sources to provide energy, and they have attracted much attention during use because of their environmental friendliness, high energy efficiency, and wide range of applications. During the operation of these batteries, the energy they generate depends on the reactions occurring at the two poles. For example, the oxygen reduction reaction (ORR), as an important cathode reaction in fuel cells and metal-air batteries, has the disadvantages of slow reaction kinetics due to multi-stage and slow reactions and low material transfer efficiency. Therefore, it requires highly active catalysts to reduce the reaction barrier and optimize the adsorption and desorption of intermediate substances to enhance the reaction. Compared with traditional single-atom catalysts, diatomic catalysts have the advantages of higher catalytic reaction activity and reaction stability, which can be more conducive to the catalytic reaction, and therefore have better application prospects.
[0004] The Chinese invention patent with application publication number CN115704097A discloses a preparation method and use of a diatomic catalyst with a MaMb-carrier structure, wherein a dinuclear complex is loaded on a carrier as a precursor and obtained by high-temperature pyrolysis under an inert atmosphere; wherein the catalytic active sites Ma and Mb are loaded on the carrier in an atomic state, respectively, and the distance between the two metal atoms is 2-4 Å, and the carrier is a carbon-based carrier or a metal oxide. The application discloses a technical solution for atomically dispersing two metal atoms, but the technical solution can only regulate the distance between two metal atoms in the same dinuclear complex; in addition, the diatomic catalyst in this application is obtained by loading a plurality of small molecule dinuclear complexes on a carrier and pyrolyzing them at high temperature. During the high-temperature pyrolysis process, the metals tend to agglomerate, so that the distance between each complex cannot be precisely regulated. In addition, the application mentions the synthesis of small molecule complexes, and therefore does not have the structural characteristics of long-chain order of macromolecular polymers. Summary of the invention
[0005] The purpose of the present invention is to regulate the distance between metal atoms in a metal diatomic polymer catalyst. In view of the above-mentioned deficiencies in the prior art, a preparation method and application of a metal diatomic polymer catalyst are proposed.
[0006] A metal diatomic polymer catalyst, which is composed of a polymer obtained by reacting a monomer one and a monomer two, and a complexed metal ion. The monomer one is an aromatic monomer containing a thiol group and an aldehyde group or an aromatic monomer containing a hydroxyl group and an aldehyde group, and the monomer two is an aromatic tetraamine or hexamine monomer.
[0007] The above technical scheme is further configured as follows: the aromatic monomer containing hydroxyl and aldehyde groups is one of 2-hydroxyisophthalaldehyde, 1,8-dihydroxy-2,7-naphthalenedicarbaldehyde, and 1,9-dihydroxy-2,8-anthracenedicarboxaldehyde; the aromatic monomer containing thiol and aldehyde groups is one of 1,3-phthalaldehyde-2-thiol, 1,8-dithiol-2,7-naphthalenedicarbaldehyde, and 1,9-dithiol-2,8-anthracenedicarboxaldehyde.
[0008] The above technical scheme is further configured as follows: the aromatic tetraamine or hexamine monomer is one of 1,2,4,5-benzenetetramine, 2,3,6,7-tetraaminonaphthalene, anthracene-2,3,6,7-tetramine, 4,5,9,10-tetraaminopyrene, and 2,3,6,7,10,11-hexaaminotriphenyl.
[0009] The above technical solution is further configured as follows: the metal is one or more of Mg, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sn, Ru, Rh, Pd, Ir, Pt, Ag, and Au.
[0010] A method for preparing a metal diatomic polymer catalyst, characterized in that it comprises the following steps: S1, mixing the methanol solution of monomer 1 with the methanol solution of metal ions, and mixing them evenly to obtain a mixed solution; S2, slowly dropwise adding the methanol solution of monomer 2 to the mixed solution obtained in step S1, and condensing and refluxing until crystals precipitate; S3. Filter, wash and dry the crystals obtained in step S2 to obtain a homogeneous bimetallic atom polymer M-DP.
[0011] The above technical scheme is further configured as follows: when the monomer 2 is a tetraamine monomer, the molar ratio of the monomer 1, the tetraamine monomer 2 and the metal ion is (1.8-2.2):1:(1.8-2.2); when the monomer 2 is a hexamine monomer, the molar ratio of the monomer 1, the hexamine monomer 2 and the metal ion is (2.8-3.2):1:(2.8-3.2).
[0012] The method for preparing a metal diatomic polymer catalyst is characterized by comprising the following steps: S1, mixing the methanol solution of monomer 1 with the methanol solution of metal Ma, and mixing them evenly to obtain a mixed solution; S2, slowly dropwise adding the methanol solution of monomer 2 to the mixed solution obtained in step S1, condensing and refluxing, and condensing and refluxing until crystals precipitate; S3, filtering, washing and drying the crystals obtained in step S2 to obtain an atomic polymer Ma-P' of the complex metal Ma; S4, dispersing the Ma-P' obtained in step S3 in a methanol solution to form a Ma-P' methanol mixed solution, and slowly dropping a methanol solution containing metal Mb into the Ma-P' methanol mixed solution to react and form a mixture; S5. When the color of the mixture in step S4 remains unchanged, the methanol solution of monomer 2 is added. After the reaction is completed, the obtained precipitate is filtered, washed, and dried to obtain a heterogeneous bimetallic atom polymer MaMb-DP.
[0013] The above technical scheme is further configured as follows: when the monomer 2 is a tetraamine monomer, the molar ratio of the monomer 1 in step S1, the tetraamine monomer 2 in step S2 and the tetraamine monomer 2 in step S5 is (3.8-4.2):1:1, and the molar ratio of the monomer 1, the metal Ma and the metal Mb is (3.8-4.2):(1.8-2.2):(1.8-2.2); when the monomer 2 is a hexamine monomer, the molar ratio of the monomer 1 in step S1, the hexamine monomer 2 in step S2 and the hexamine monomer 2 in step S5 is (5.8-6.2):1:1, and the molar ratio of the monomer 1, the metal Ma and the metal Mb is (5.8-6.2):(2.8-3.2):(2.8-3.2).
[0014] Metal diatomic polymer catalyst material uses a matrix material as a carrier and has a polymer catalyst loaded with metal atoms on the surface.
[0015] The above technical solution is further configured as follows: the matrix material includes one or more of conductive carbon black, carbon nanotubes, activated carbon, Ketjen black, graphene, carbon cloth, carbon fiber, cotton fabric, polyester, nylon, wool, silk, glass fiber cloth, aramid fiber cloth, and polypropylene.
[0016] The beneficial effects of the present invention are: 1. Aromatic monomers containing aldehyde groups and hydroxyl groups / thiol groups react with aromatic tetraamine or hexamine monomers to form polymers connected by aromatic rings. The polymers are then complexed with metal ions. The metal ions coordinate with two nitrogen atoms on the Schiff base structure and two oxygen atoms from ionized phenolic hydroxyl groups or two sulfur atoms on mercaptobenzene to form metal diatomic linear or planar polymers composed of planar structural units of [MaMbN4X2] or [MaMbN4X4], where X is an O atom or an S atom. Since the polymer is synthesized using a non-thermal decomposition strategy throughout the synthesis process, the polymer has a linear or planar long chain structure consistent with the original design, and has a regular structure that can anchor multiple metal atoms.
[0017] 2. In the catalytic reaction process, the catalytic material needs to have a suitable adsorption capacity for the reaction intermediates (such as *O, *OOH, *OH in the catalytic ORR process). If the adsorption capacity of the catalytic material is too strong, the catalytic product will be adsorbed on the catalytic material, which is not easy to remove, occupying the active site and reducing the subsequent catalytic efficiency; if the adsorption capacity of the catalytic material is too weak, it will not play a catalytic role; the present invention adjusts the spacing between the metal diatoms in the repeating unit of the polymer or the spacing between two adjacent repeating units by changing the type of monomer one or monomer two to optimize the adsorption and desorption capacity of the catalytic material for the intermediates in the entire reaction process, thereby improving the catalytic performance of the metal atom catalytic material, reducing the reaction energy barrier, and promoting the reaction. On the other hand, the change in the spacing will also cause the electronic structure of the d orbital of the metal as the active site to change, thereby affecting the catalytic activity of the active site.
[0018] 3. The synthesized metal atom polymer catalyst can be compounded with different carriers to obtain different metal atom polymer catalyst materials according to different needs. The polymer can be synthesized in situ on the carrier. The entire preparation process does not require pyrolysis and the active sites are well preserved.
[0019] 4. By changing the type of monomer two, the distance between two adjacent [MaMbN4X2] or [MaMbN4X4] planar structures in the metal diatomic polymer can be adjusted. The distance between two adjacent [MaMbN4X2] or [MaMbN4X4] planar structures will affect the catalytic performance of the metal diatoms. By selecting suitable monomer two, the catalytic performance of the metal diatoms in the [MaMbN4X2] or [MaMbN4X4] planar structure can be further adjusted. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 This is a transmission electron microscope scan of the catalyst in Examples 4-5 of this application. Figure 1 a is a transmission electron microscope scanning image of S-Co@CNT in Example 4, Figure 1 b is a transmission electron microscope scanning image of the L-Co@CNT catalyst in Example 5; Figure 2 This is a spherical aberration corrected transmission electron microscope scan of the S-Co@CNT catalyst in Example 4; Figure 3 The linear sweep voltammetric curves of oxygen reduction of the catalysts in Examples 4-5 and the commercial Pt / C catalyst in 0.1 M KOH electrolyte; Figure 4 The hydrogen peroxide yield and the electron transfer number of the catalysts in Examples 4-5 and the commercial Pt / C catalyst in 0.1 M KOH electrolyte. DETAILED DESCRIPTION
[0022] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0023] The method for preparing a metal diatomic polymer catalyst is characterized by comprising the following steps, measured by molar fractions: S1, mixing 1.8-3.2 parts of a methanol solution of monomer 1 with 1.8-3.2 parts of a methanol solution of metal ions, and mixing them evenly to obtain a mixed solution; S2, slowly dropwise adding 1 portion of the methanol solution of monomer 2 to the mixed solution obtained in step S1, and condensing and refluxing until crystals precipitate; S3. Filter, wash and dry the crystals obtained in step S2 to obtain a homogeneous bimetallic atom polymer M-DP.
[0024] The monomer 1 is one of 2-hydroxyisophthalaldehyde, 1,8-dihydroxy-2,7-naphthalenedicarbaldehyde, 1,9-dihydroxy-2,8-anthracenedicarboxaldehyde, 1,3-phthalaldehyde-2-mercapto, 1,8-dimercapto-2,7-naphthalenedicarbaldehyde, and 1,9-dimercapto-2,8-anthracenedicarboxaldehyde.
[0025] 1,3-Benzenedicarboxaldehyde-2-thiol, 1,8-dimercapto-2,7-naphthalenedicarboxaldehyde, and 1,9-dimercapto-2,8-anthracenedicarboxaldehyde are prepared from the corresponding 2-hydroxyisophthalaldehyde, 1,8-dihydroxy-2,7-naphthalenedicarboxaldehyde, and 1,9-dihydroxy-2,8-anthracenedicarboxaldehyde. The reaction mechanism of the preparation is as follows:
[0026] Monomer 2 is one of 1,2,4,5-benzenetetramine, 2,3,6,7-tetraaminonaphthalene, anthracene-2,3,6,7-tetramine, 4,5,9,10-tetraaminopyrene, and 2,3,6,7,10,11-hexaaminotriphenyl.
[0027] The homogeneous bimetallic atom polymer M-DP is prepared by using 2-hydroxyisophthalaldehyde as monomer one and 1,2,4,5-benzenetetramine as monomer two. The reaction equation is as follows:
[0028] The homogeneous bimetallic atom polymer M-DP was prepared by using 1,3-benzenedicarboxylic acid-2-thiol as monomer one and 1,2,4,5-benzenetetramine as monomer two. The reaction equation is as follows:
[0029] The homogeneous bimetallic atom polymer M-DP was prepared by using 1,8-dihydroxy-2,7-naphthalene dicarboxaldehyde as monomer one and 1,2,4,5-benzene tetramine as monomer two. The reaction equation is as follows:
[0030] The homogeneous bimetallic atom polymer M-DP was prepared by using 1,8-dimercapto-2,7-naphthalenedicarbaldehyde as monomer one and 1,2,4,5-benzenetetramine as monomer two. The reaction equation is as follows:
[0031] The homogeneous bimetallic atom polymer M-DP was prepared by using 1,9-dihydroxy-2,8-anthracene dicarboxaldehyde as monomer one and 1,2,4,5-benzene tetramine as monomer two. The reaction equation is as follows:
[0032] The homogeneous bimetallic atom polymer M-DP was prepared by using 1,9-dimercapto-2,8-anthracene dicarboxaldehyde as monomer one and 1,2,4,5-benzenetetramine as monomer two. The reaction equation is as follows:
[0033] It can be seen from Formulas 1 to 6 that by replacing monomer 1, the distance between two metal atoms in the [M2N4X2] or [M2N4X4] structural unit of the polymer can be regulated.
[0034] The homogeneous bimetallic atom polymer M-DP was prepared by using 2-hydroxyisophthalaldehyde as monomer one and 2,3,6,7-tetraaminonaphthalene as monomer two. The reaction equation is as follows:
[0035] The homogeneous bimetallic atom polymer M-DP was prepared by using 1,3-benzenedicarboxaldehyde-2-thiol as monomer one and 2,3,6,7-tetraaminonaphthalene as monomer two. The reaction equation is as follows:
[0036] The homogeneous bimetallic atom polymer M-DP was prepared by using 2-hydroxyisophthalaldehyde as monomer one and anthracene-2,3,6,7-tetraamine as monomer two. The reaction equation is as follows:
[0037] The homogeneous bimetallic atom polymer M-DP was prepared by using 1,3-benzenedicarboxaldehyde-2-thiol as monomer one and anthracene-2,3,6,7-tetraamine as monomer two. The reaction equation is as follows:
[0038] It can be seen from Formula 1, Formula 2, Formula 7 to Formula 10 that by replacing monomer 2, the distance between metal atoms between two adjacent structural units in the polymer can be regulated.
[0039] The homogeneous bimetallic atom polymer M-DP was prepared by using 2-hydroxyisophthalaldehyde as monomer 1 and 2,3,6,7,10,11-hexaaminotriphenyl as monomer 2. The reaction equation is as follows:
[0040] The homogeneous bimetallic atom polymer M-DP was prepared by using 1,3-benzenedicarboxylic-2-thiol as monomer 1 and 2,3,6,7,10,11-hexaaminotriphenyl as monomer 2. The reaction equation is as follows:
[0041] It can be seen from Formula 11 and Formula 12 that by using aromatic hexamine as monomer 2, a metal diatomic planar polymer can be obtained.
[0042] The method for preparing a metal diatomic polymer catalyst is characterized by comprising the following steps, measured by molar fractions: S1, mixing a methanol solution containing 3.8-6.2 parts of monomer 1 with a methanol solution containing 1.8-3.2 parts of metal Ma, and mixing them evenly to obtain a mixed solution; S2, slowly dropwise adding a methanol solution containing 1 part of monomer 2 into the mixed solution obtained in step S1, and condensing and refluxing until crystals precipitate; S3, filtering, washing and drying the crystals obtained in step S2 to obtain an atomic polymer Ma-P' of the complex metal Ma; S4, dispersing the Ma-P' obtained in step S3 in a methanol solution to form a Ma-P' methanol mixed solution, slowly dropping a methanol solution containing 1.8-3.2 parts of metal Mb into the Ma-P' methanol mixed solution to react and form a mixture; S5. When the color of the mixture in step S4 remains unchanged, add a methanol solution containing 1 part of monomer 2. After the reaction is completed, filter, wash and dry the obtained precipitate to obtain a heterogeneous bimetallic atom polymer MaMb-DP.
[0043] The heterogeneous bimetallic atom polymer M-DP was prepared by using 2-hydroxyisophthalaldehyde as monomer one and 1,2,4,5-benzenetetramine as monomer two. The reaction equation is as follows:
[0044] The heterogeneous bimetallic atom polymer M-DP was prepared by using 1,3-benzenedicarboxylic acid-2-thiol as monomer one and 1,2,4,5-benzenetetramine as monomer two. The reaction equation is as follows:
[0045] In step S1, the molar ratio of monomer one to monomer two is close to 4:1. One mole of monomer two can react with four moles of monomer one to first generate a small molecule compound as shown in Formula 13 or Formula 14. Each small molecule compound contains four vacancies that can complex metal atoms. Two moles of metal Ma are added to the small molecule compound. Metal Ma first occupies two vacancies in the small molecule compound as shown in Formula 13 or Formula 14 to form two [MaN2X2O2] structures, where X is an O atom or an S atom. Because the energy required for metal Ma to enter another vacancy in the [MaN2X2O2] structure is higher, the metal ions preferentially form a single metal atom polymer Ma-P'.
[0046] Then, 2 mol of a methanol solution of metal Mb is slowly added to the single metal atom polymer Ma-P', as shown in Formula 13 or Formula 14. Metal Mb will complex with another vacancy in the [MaN2X2O2] structure to obtain a small molecule compound containing two [MaMbN2X2O2] structures.
[0047] In step S5, one part of monomer 2 is added to the mixture, and monomer 2 can connect the two small molecular compounds containing the [MaMbN2X2O2] structure in step S4 to each other to obtain a macromolecular polymer with the structure of [MaMbN4X2].
[0048] The heterogeneous bimetallic atom polymer M-DP was prepared by using 2-hydroxyisophthalaldehyde as monomer 1 and 2,3,6,7,10,11-hexaaminotriphenylene as monomer 2. The reaction equation is as follows:
[0049] The heterogeneous bimetallic atom polymer M-DP was prepared by using 1,3-benzenedicarboxylic-2-thiol as monomer 1 and 2,3,6,7,10,11-hexaaminotriphenyl as monomer 2. The reaction equation is as follows:
[0050] In step S1, the molar ratio of monomer one to monomer two is close to 6:1. One mole of monomer two can react with six moles of monomer one to first generate a small molecule compound as shown in Formula 15 or Formula 16. Each small molecule compound contains six vacancies that can complex metal atoms. Three moles of metal Ma are added to the small molecule compound. Metal Ma first occupies three vacancies in the small molecule compound as shown in Formula 15 or Formula 16 to form three [MaN2X2O2] structures, where X is an O atom or an S atom. Because the energy required for metal Ma to enter another vacancy in the [MaN2X2O2] structure is higher, the metal ions preferentially form a single metal atom polymer Ma-P'. Then, 3 mol of a methanol solution of metal Mb is slowly added to the single metal atom polymer Ma-P', as shown in Formula 15 or Formula 16. Metal Mb will complex with another vacancy in the [MaN2X2O2] structure to obtain a small molecule compound containing three [MaMbN2X2O2] structures.
[0051] In step S5, one portion of monomer 2 is added to the mixture. Monomer 2 can connect the three small molecular compounds containing the [MaMbN2X2O2] structure in step S4 to each other to obtain a macromolecular polymer with the structure of [MaMbN4X2].
[0052] 1. Preparation method Example 1 Synthesis of homogeneous dimetallic atoms: In terms of molar proportions, 2 parts of a methanol solution of Co(NO3)2·6H2O were mixed with a methanol solution containing 2 parts of 2-hydroxyisophthalaldehyde. After the solutions were evenly mixed, 1 part of a methanol solution of 1,2,4,5-benzenetetramine was slowly added to the above-mentioned uniform solution. The mixture was condensed and refluxed, and orange crystals were found to be precipitated. Subsequently, the homogeneous dimetallic atom polymer Co-DP was obtained by filtration, washing and drying.
[0053] Example 2 Synthesis of heterogeneous bimetallic atoms: According to molar proportions, 2 parts of Co(NO3)2·6H2O methanol solution were mixed with 4 parts of 2-hydroxyisophthalaldehyde methanol solution. After the solution was evenly mixed, 1 part of 1,2,4,5-benzenetetramine methanol solution was slowly added to the above-mentioned uniform solution, condensed and refluxed, and orange crystals were found to precipitate. Then, the small molecule compound Co-P' was obtained by filtration and washing. Co-P' was added to the methanol solution to form a uniformly mixed solution. Under the protection of argon atmosphere, 2 parts of FeCl2·4H2O methanol solution were slowly added dropwise. When the color of the mixture did not change, 1 part of 1,2,4,5-benzenetetramine methanol solution was added. After a while, the obtained precipitate was filtered, washed and dried to obtain the heterogeneous bimetallic atom polymer CoFe-DP.
[0054] Example 3 Synthesis of planar bimetallic atom polymer catalyst material: In terms of molar parts, carbon nanotubes are dispersed in a methanol solution, 3 parts of a methanol solution of 2-hydroxyisophthalaldehyde are slowly dropped into the stirring carbon nanotube dispersion, and then 3 parts of Co(NO3)2·6H2O are added to the above-mentioned uniform solution. After a uniform dispersion is formed, 1 part of a methanol solution of 2,3,6,7,10,11-hexaaminotriphenylene is slowly dropped into the solution, and then the obtained uniform solution is condensed and refluxed, followed by filtration, washing and drying to obtain carbon nanotubes loaded with a homogeneous bimetallic atom planar polymer Co-DP.
[0055] Example 4 Synthesis of linear bimetallic atom polymer catalyst material: According to the molar ratio, carbon nanotubes are dispersed in a methanol solution, 2 parts of a methanol solution of 2-hydroxyisophthalaldehyde are slowly dropped into the stirring carbon nanotube dispersion, and then 2 parts of Co(NO3)2·6H2O are added to the above-mentioned uniform solution. After a uniform dispersion is formed, 1 part of a methanol solution of 1,2,4,5-benzenetetramine is slowly dropped into the solution, and then the obtained uniform solution is condensed and refluxed, followed by filtration, washing and drying to obtain carbon nanotubes loaded with a homogeneous bimetallic atom linear polymer Co-DP, named S-Co@CNT.
[0056] Example 5 Synthesis of linear bimetallic atom polymer catalyst material: In terms of molar parts, carbon nanotubes are dispersed in a methanol solution, 2 parts of a methanol solution of 1,8-dihydroxy-2,7-naphthalenedicarboxylic acid are slowly added to the stirring carbon nanotube dispersion, and then 2 parts of Co(NO3)2·6H2O are added to the above-mentioned uniform solution. After a uniform dispersion is formed, 1 part of a methanol solution of 1,2,4,5-benzenetetramine is slowly added to the solution, and then the obtained uniform solution is condensed and refluxed for 3 hours, followed by filtration, washing and drying to obtain carbon nanotubes loaded with a homogeneous bimetallic atom linear polymer Co-DP, named L-Co@CNT.
[0057] II. Analysis of test results of various embodiments (1) The S-Co@CNT catalysts obtained in Example 4 and the L-Co@CNT catalysts obtained in Example 5 were scanned by transmission electron microscope to obtain Figure 1 , Figure 1 a is the transmission electron microscope scanning image of S-Co@CNT, Figure 1 b is the transmission electron microscope scanning image of L-Co@CNT. Figure 1 a and Figure 1 The successful composite of polymer and carbon nanotubes can be seen in b.
[0058] (2) Figure 2 This is a spherical aberration-corrected transmission electron microscopy scan of the S-Co@CNT catalyst. Figure 2 Pairs of metal atoms can be observed in the sample, and no agglomeration of metal atoms is found, which proves the uniform distribution of atoms.
[0059] (3) The oxygen reduction performance of the S-Co@CNT obtained in Example 4, the L-Co@CNT catalyst obtained in Example 5, and the commercial Pt / C catalyst was tested using a rotating disk electrode. The specific test method was as follows: the temperature was 25°C, the electrolyte used was an oxygen-saturated 0.1 M KOH aqueous solution, and the working electrode was an area of 0.19625 cm -2 The glassy carbon rotating disk electrode rotates at 1600 rpm; the counter electrode is a carbon rod, and the reference electrode is a saturated Ag / AgCl electrode. The reference electrode potential is calibrated by a reversible hydrogen electrode. Weigh 6 mg of catalyst, add 970 μL of ethanol and 30 μL of 5% Nafion solution for ultrasonic dispersion to prepare a catalyst slurry, drop 20 μL of catalyst ink on the rotating disk electrode, and dry naturally. The scan rate for oxygen reduction test is 10 mV s -1 The results of the rotating disk electrode test of the catalyst are shown in Figure 3 , Figure 4 and Table 1.
[0060] Table 1 Rotating disk electrode test results of the catalysts in Examples 4-5 and commercial Pt / C catalysts
[0061] It can be seen from Table 1 that the catalytic activity is affected by regulating the distance between the two metal atoms. The half-wave potential of the S-Co@CNT catalyst is 0.973 V, which is higher than 0.907 V of the L-Co@CNT catalyst and higher than 0.875 V of the commercial Pt / C catalyst.
[0062] from Figure 3 It can be seen that the half-wave potential and limiting current density of the S-Co@CNT catalyst and the L-Co@CNT catalyst are higher than those of the commercial Pt / C catalyst, and the half-wave potential and limiting current density of the S-Co@CNT catalyst are the highest.
[0063] from Figure 4 It can be seen that the selectivity of the S-Co@CNT catalyst and the L-Co@CNT catalyst is slightly lower than that of the commercial Pt / C catalyst, but the selectivity of the S-Co@CNT catalyst is higher than that of the L-Co@CNT catalyst, indicating that the S-Co@CNT has a higher four-electron selectivity.
[0064] For matters not mentioned above, the prior art applies.
[0065] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A metal diatomic polymer catalyst, characterized in that: The metal diatomic polymer catalyst is composed of a polymer obtained by reacting monomer one and monomer two, and a complex metal ion. The monomer one is an aromatic monomer containing a thiol group and an aldehyde group or an aromatic monomer containing a hydroxyl group and an aldehyde group, and the monomer two is an aromatic tetraamine or hexamine monomer.
2. The metal diatomic polymer catalyst according to claim 1, characterized in that: The aromatic monomer containing hydroxyl and aldehyde groups is one of 2-hydroxyisophthalaldehyde, 1,8-dihydroxy-2,7-naphthalene dicarboxaldehyde, and 1,9-dihydroxy-2,8-anthracene dicarboxaldehyde; the aromatic monomer containing thiol and aldehyde groups is one of 1,3-phthalaldehyde-2-thiol, 1,8-dithiol-2,7-naphthalene dicarboxaldehyde, and 1,9-dithiol-2,8-anthracene dicarboxaldehyde.
3. The metal diatomic polymer catalyst according to claim 1, characterized in that: The aromatic tetraamine or hexamine monomer is one of 1,2,4,5-phenyltetraamine, 2,3,6,7-tetraaminonaphthalene, anthracene-2,3,6,7-tetraamine, 4,5,9,10-tetraaminopyrene and 2,3,6,7,10,11-hexaaminotriphenyl.
4. The metal diatomic polymer catalyst according to claim 1, characterized in that: The metal is one or more of Mg, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sn, Ru, Rh, Pd, Ir, Pt, Ag, and Au.
5. A method for preparing the metal diatomic polymer catalyst according to any one of claims 1 to 4, characterized in that: The steps include: S1, mixing the methanol solution of monomer 1 and the methanol solution of metal ions uniformly to obtain a mixed solution; S2, slowly dropwise adding the methanol solution of monomer 2 to the mixed solution obtained in step S1, and condensing and refluxing until crystals precipitate; S3. Filter, wash and dry the crystals obtained in step S2 to obtain a homogeneous bimetallic atom polymer M-DP.
6. The method for preparing a metal atom polymer catalyst with adjustable atomic spacing according to claim 5, characterized in that: When the monomer 2 is a tetraamine monomer, the molar ratio of the monomer 1, the tetraamine monomer 2 and the metal ion is (1.8-2.2):1:(1.8-2.2); when the monomer 2 is a hexamine monomer, the molar ratio of the monomer 1, the hexamine monomer 2 and the metal ion is (2.8-3.2):1:(2.8-3.2).
7. A method for preparing the metal diatomic polymer catalyst according to any one of claims 1 to 4, characterized in that: The steps include: S1, mixing the methanol solution of monomer 1 and the methanol solution of metal Ma uniformly to obtain a mixed solution; S2, slowly dropwise adding the methanol solution of monomer 2 to the mixed solution obtained in step S1, condensing and refluxing, and condensing and refluxing until crystals precipitate; S3, filtering, washing and drying the crystals obtained in step S2 to obtain an atomic polymer Ma-P' of the complex metal Ma; S4, dispersing the Ma-P' obtained in step S3 in a methanol solution to form a Ma-P' methanol mixed solution, slowly dropping a methanol solution of metal Mb into the Ma-P' methanol mixed solution to react and form a mixture; S5. When the color of the mixture in step S4 remains unchanged, the methanol solution of monomer 2 is added. After the reaction is completed, the obtained precipitate is filtered, washed and dried to obtain a heterogeneous bimetallic atom polymer MaMb-DP.
8. The method for preparing the metal diatomic polymer catalyst according to claim 7, characterized in that: When the monomer 2 is a tetraamine monomer, the molar ratio of the monomer 1 in step S1, the tetraamine monomer 2 in step S2 and the tetraamine monomer 2 in step S5 is (3.8-4.2):1:1, and the molar ratio of the monomer 1, the metal Ma and the metal Mb is (3.8-4.2):(1.8-2.2):(1.8-2.2); when the monomer 2 is a hexamine monomer, the molar ratio of the monomer 1 in step S1, the hexamine monomer 2 in step S2 and the hexamine monomer 2 in step S5 is (5.8-6.2):1:1, and the molar ratio of the monomer 1, the metal Ma and the metal Mb is (5.8-6.2):(2.8-3.2):(2.8-3.2).
9. A metal diatomic polymer catalyst material, characterized in that: The matrix material is used as a carrier, and the metal atom polymer catalyst with adjustable atomic spacing as described in any one of claims 1 to 5 is loaded on the surface.
10. The metal diatomic polymer catalyst material according to claim 9, characterized in that: The matrix material includes one or more of conductive carbon black, carbon nanotubes, activated carbon, Ketjen black, graphene, carbon cloth, carbon fiber, cotton fabric, polyester, nylon, wool, silk, glass fiber cloth, aramid fiber cloth, and polypropylene.
Citation Information
Patent Citations
Bimetal complexes of phenoxy imine ligand framework, preparation method and application
CN111943973A
Photocatalytic synthesis method of benzimidazolyl covalent organic framework material
CN114456338A
Preparation method and application of diatomic catalyst with M1M2-carrier structure
CN115704097A